2013
DOI: 10.1016/j.str.2013.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Functions of TBK1 in Innate Antimicrobial Immunity

Abstract: SUMMARY Tank-binding kinase 1 (TBK1) is a serine/threonine protein kinase mediating innate antimicrobial immunity. TBK1 is involved in the signaling of TLRs, RLRs, and STING-mediated sensing of cytosolic DNA. Stimulation of these receptors results in the activation of TBK1, which phosphorylates interferon regulatory factor IRF-3. Phosphorylated IRF-3 translocates into the nucleus to initiate the transcription of the IFN-β gene. Here we show that TBK1 is activated by autophosphorylation at residue Ser172. Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 49 publications
5
97
0
Order By: Relevance
“…The IRF-3/CBP dimer structure also explains how dozens of previously reported mutations affect IRF-3 activation (Fig. S5F) (27,29,(32)(33)(34). Most of these mutations are located at the tail-mediated IRF-3 dimer interface and play crucial roles in mediating IRF-3 dimerization (Fig.…”
Section: Irf-3 (23)mentioning
confidence: 78%
See 2 more Smart Citations
“…The IRF-3/CBP dimer structure also explains how dozens of previously reported mutations affect IRF-3 activation (Fig. S5F) (27,29,(32)(33)(34). Most of these mutations are located at the tail-mediated IRF-3 dimer interface and play crucial roles in mediating IRF-3 dimerization (Fig.…”
Section: Irf-3 (23)mentioning
confidence: 78%
“…Binding of the phospho-pLxIS motif to IRF-3 induces conformational changes that begin to reorganize key IRF-3 loops and uncover surfaces involved in dimerization, whereas colocalization of IRF-3 with TBK1 induces phosphorylation of the pLxIS motif in the IRF-3 tail. Phosphorylation of IRF-3 by TBK1 can occur in vitro but is relatively inefficient and requires high concentrations (34); colocalization of TBK1 and IRF-3 through recruitment via the adaptors increases local concentrations of both, thus facilitating the phosphorylation and dimerization of IRF-3. The scaffold mechanism for IRF-3 activation would protect effectively against the activation of IRF-3 in the cytosol by TBK1 until appropriate formation of the innate signaling machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though a mass spectrometry scan has suggested that Thr75 and Thr253 of IRF3 might be phosphorylated in cells (Shu et al 2013), the function implications of the phosphorylation and the kinases responsible for Thr75 or Thr253 modification have not been explored. The Thr75 residue is located in the DBD of IRF3; thus, it is not surprising that its phosphorylation disrupts DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…TBK1 is a member of the IKK-related kinases and is a known upstream mediator of non-canonical NF-B activation (29). TBK1 contains an autophosphorylation site at Ser 172 , which is indicative of TBK1 kinase activation (30). To determine the effects of fumarate on TBK1 activation, we treated DKO IKK␣/␤ MEFs with increasing concentrations of DEF.…”
Section: Resultsmentioning
confidence: 99%